Witches and witchcraft - Nash, David (David S.) (Oxford, U.K. ; New York, NY : Shire Publications, 2014)
Witchcraft and society's attitudes to it haunt the Western imagination to this day, from Central Europe to Britain to North America. This book explores the development of witchcraft and of the belief in it (stressing the difference between the two), the sixteenth and seventeenth century obsession that spawned witch-hunting, the eventual decline of witchcraft, and the phenomenon's fascinating 'afterlife' that has involved the Nazis' fixation and modern treatments including Arthur Miller's acclaimed 'The Crucible'. Fully illustrated with historical documents and colour photographs, and expert.
Includes bibliographical references and index.
Keywords: Witchcraft; Witch hunting -- History; Witches; Witchcraft -- Social aspects -- History; Witches -- History; Witchcraft -- History